2008
DOI: 10.1007/s11627-008-9147-9
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Aeschynanthus radicans via direct somatic embryogenesis and analysis of regenerants with flow cytometry

Abstract: Plant regeneration through direct somatic embryogenesis in Aeschynanthus radicans 'Mona Lisa' was achieved in this study. Globular somatic embryos were formed directly from cut edges of leaf explants and cut ends or on the surface of stem explants 4 wk after culture on Murashige and Skoog (MS) medium supplemented with N-phenyl-N′-1, 2, 3-thiadiazol-5-ylurea (TDZ) with α-naphthalene acetic acid (NAA), TDZ with 2,4-dichlorophenoxyacetic acid (2,4-D), or 6-benzylaminopurine (BA) or kintin (KN) with 2,4-D. MS medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…Similarly, the research made into the evaluation of genetic stability of Mammillaria san-angelensis regenerants induced by auxin in long-term in vitro culture (Palomino et al 1999) and of microcuttings of chrysanthemums obtained from somatic embryos also point to no effect of auxin 2,4-D on the genetic stability of plants (Lema-Rumińska and Ś liwińska 2009). The stability of plants Aeschynanthus radicans produced from somatic embryos was also reported by Cui et al (2009) using the flow cytometer.…”
Section: Analysis With Flow Cytometrymentioning
confidence: 81%
“…Similarly, the research made into the evaluation of genetic stability of Mammillaria san-angelensis regenerants induced by auxin in long-term in vitro culture (Palomino et al 1999) and of microcuttings of chrysanthemums obtained from somatic embryos also point to no effect of auxin 2,4-D on the genetic stability of plants (Lema-Rumińska and Ś liwińska 2009). The stability of plants Aeschynanthus radicans produced from somatic embryos was also reported by Cui et al (2009) using the flow cytometer.…”
Section: Analysis With Flow Cytometrymentioning
confidence: 81%
“…In this study, TDZ was more effective for callus proliferation of S. alfredii than BA. TDZ, first introduced as a cotton defoliant and later demonstrated to possess cytokinin-like activity (Mok et al 1979;Thomas and Katterman 1986), has long been reported to exhibit stronger activity in inducing cellular differentiation in a wide range of plant species (Amutha et al 2006;Yookongkaew et al 2007;Cui et al 2009). In this study, callus fresh weight gradually increased when explants were grown in the presence of combinations of 2,4-D and BA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence suggests that somatic embryogenesis has a multicellular origin that may result in chromosomal alterations or ploidy changes (Endemann et al 2001;Tremblay et al 1999). Therefore, detection of such variation early in the life of a plant would be required to avoid economic disaster for commercial regeneration of broccoli plants (Cui et al 2009;Qin et al 2007). …”
Section: Introductionmentioning
confidence: 99%